Study of the strength of soft clay reinforced with single encapsulated bottom ash columns - Nurain Zahidah, Nazarudin (2015)
Stone column is one of the ground improvement techniques that are environmental friendly with effective cost and viable to reduce settlement of foundations on cohesive soft soil. Installation of stone column can increase the bearing capacity and the shear resistance of the soil mass. Bottom ash is the waste of coal burning generally is a coarse, granular in shape material that is used as stone columns and it is probably reducing usage of non-renewable material such as stone and sand. Besides that, by introducing bottom ash columns, sustainability can be achieved and the disposal problem for bottom ash can be solved. This paper discusses the results of the strength of soft clay reinforced with single encapsulated bottom ash columns. A total of six (6) batches of kaolin samples had been tested to determine the shear strength. Each batch consisted of three (3) samples to represent different size of height of bottom ash columns. A total of 18 unconsolidated- undrained triaxial tests had been conducted on soft kaolin specimens. The specimens were used in this project is 38 mm in diameter and 76 mm in height. The diameter of the bottom ash columns is 6 mm and 8 mm and the heights of the column are 38 mm, 57 mm and 76 mm. For diameter of the bottom ash columns 6 mm, the value of strength parameters of soft clay inserted with 38 mm height of the columns increased more significant compared to the fully penetrating column which is 76 mm in height of the columns. The diameter of the bottom ash columns 8 mm, the value of strength parameters of soft clay inserted with fully penetrating column which is 76 mm in height increased more significant compared to the 38 mm in height of column.